Fate of Ingested Clostridium difficile Spores in Mice - Howerton, Amber (Public Library of Science, 2013)
Clostridium difficile infection (CDI) is a leading cause of antibiotic-associated diarrhea, a major nosocomial complication. The infective form of C. difficile is the spore, a dormant and resistant structure that forms under stress. Although spore germination is the first committed step in CDI onset, the temporal and spatial distribution of ingested C. difficile spores is not clearly understood. We recently reported that CamSA, a synthetic bile salt analog, inhibits C. difficile spore germination in vitro and in vivo. In this study, we took advantage of the anti-germination activity of bile salts to determine the fate of ingested C. difficile spores. We tested four different bile salts for efficacy in preventing CDI. Since CamSA was the only anti-germinant tested able to prevent signs of CDI, we characterized CamSa’s in vitro stability, distribution, and cytotoxicity. We report that CamSA is stable to simulated gastrointestinal (GI) environments, but will be degraded by members of the natural microbiota found in a healthy gut. Our data suggest that CamSA will not be systemically available, but instead will be localized to the GI tract. Since in vitro pharmacological parameters were acceptable, CamSA was used to probe the mouse model of CDI. By varying the timing of CamSA dosage, we estimated that C. difficile spores germinated and established infection less than 10 hours after ingestion. We also showed that ingested C. difficile spores rapidly transited through the GI tract and accumulated in the colon and cecum of CamSA-treated mice. From there, C. difficile spores were slowly shed over a 96-hour period. To our knowledge, this is the first report of using molecular probes to obtain disease progression information for C. difficile infection.